Secularization of Islam in Post-Revolutionary Iran - Pargoo, Mahmoud (Iranian Studies, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- Acknowledgments -- Introduction -- Chapter 1 What is Islamic secularity? -- Chapter 2 Pioneers of Islamic secularity -- Chapter 3 Khomeini's revolt against secularity -- Chapter 4 Post-Khomeini: Secularization resumes -- Conclusion -- Appendix -- Bibliography -- Index.